Efficacy of hydroxychloroquine for treating annular erythema associated with Sjögren's syndrome. Issue 10 (12th July 2021) - Arakawa, Hiroki; Tanese, Keiji; Tanaka, Ryo; Murakami, Kaori; Sujino, Kazuyo; Miyamoto, Julia; Amagai, Masayuki; Tanikawa, Akiko
Abstract: Annular erythema is one of the cutaneous manifestations of Sjögren's syndrome (SS). Topical corticosteroids and tacrolimus, and oral corticosteroids, have been used as treatments for this condition. However, the safety and efficacy of these treatments remains unsatisfactory, and further development of therapies are desired. In this study, we performed a retrospective analysis of 16 annular erythema associated with SS (AESS) patients treated with hydroxychloroquine (HCQ). Disease activity was assessed using a modified version of the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI), which we termed the modified CLASI (m‐CLASI). HCQ treatment improved AESS lesions in all 16 patients. The mean m‐CLASI score was reduced by 85.6% at the 12‐week follow‐up relative to baseline ( p  < 0.01). Notably, 60% (6/10 cases) of patients with AESS lesions limited to the facial area achieved complete remission within 4 weeks. In the analysis of six patients who had taken oral prednisolone before starting HCQ, all were able to reduce the dose within 52 weeks without relapse. Particularly, 75% (3/4 cases) of patients with prednisolone dose of more than 5 mg/day could reduce their dose to less than 5 mg/day in combination with HCQ. For the safety concerns, two patients experienced grade 1 diarrhea during the 52‐week observation period. However, neither serious adverse events nor adverse events requiring discontinuation of treatment occurred. The results of the present study suggest that HCQ may not only be highly effective as a single agent, but may also be useful as a steroid‐sparing agent in refractory case requiring long‐term steroid administration, making it a good treatment option for AESS.